Особливості психічних змін у хворих тяжкими соматичними захворюваннями = Features of mental changes in patients with severe medical diseases - S. P. Koshova (Kazimierz Wielki University, 2016)
Koshova S. P. Особливості психічних змін у хворих тяжкими соматичними захворюваннями = Features of mental changes in patients with severe medical diseases. Journal of Education, Health and Sport. 2016;6(7):75-90. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57123 http://ojs.ukw.edu.pl/index.php/johs/article/view/3663       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016.   УДК159. 923   Особливості психічних змін у хворих тяжкими соматичними захворюваннями   С. П. Кошова   Національна медична академія післядипломної освіти імені П. Л. Шупика   Реферат У статті розглядається проблема психосоматичних захворювань, вплив значущих переживань на формування та перебіг психосоматичних розладів, особливості розвитку особистості в онтогенезі, взаємозалежність емоційної сфери психіки людини та стану її здоров'я, висвітлюються особливості психічних змін хворих при соматичних захворюваннях. Ідея про можливість впливу психічного стану на фізичне здоров'я не нова, про це говорив ще давньогрецький філософ Платон, який стверджував, що душа і тіло є єдиним цілим. Пізніше його ідеї підтримали багато вчених, і сьогодні все частіше стає зрозуміло, що наші емоції часто керують нашим фізичним станом.   Ключові слова: захисні механізми, онтогенез, психіка, емоції, суб'єктивні переживання, стрес, адаптаційні процеси, психосоматичні розлади, здоров'я людини, ієрархизованість мотивів.   Features of mental changes in patients with severe medical diseases   S. P. Koshova   Shupyk National Medical Academy of Postgaduate Education   Abstract The problem of psychosomatic diseases, the impact of significant experiences the formation and progress of psychosomatic disorders, especially the development of personality in ontogenesis, interdependence emotional sphere of the human psyche and the state of her health, mental changes, specific features of patients with somatic diseases. The idea of the possible impact on the mental state of physical health is not new, this was still the ancient Greek philosopher Platon, who argued that the soul and the body are inseparable. Later, it supported the idea many scientists today is increasingly becoming clear that our emotions often govern our physical condition.   Keywords: protective mechanisms, ontogenesis, mind, emotions and subjective experiences, stress, adaptive processes, psychosomatic disorders, health, hierarchy of motives.   Реферат ОСОБЕННОСТИ ПСИХИЧЕСКИХ ИЗМЕНЕНИЙ У БОЛЬНЫХ ТЯЖЕЛЫМИ СОСАТИЧЕСКИМИ ЗАБОЛЕВАНИЯМИ. В статье рассматривается проблема психосоматических заболеваний, влияние значимых переживаний на формирование и течение психосоматических расстройств, особенности развития личности в онтогенезе, взаимозависимость эмоциональной сферы психики человека и состояния его здоровья, освещаются особенности психических изменений больных при соматических заболеваниях. Идея о возможности влияния психического состояния на физическое здоровье не нова, об этом говорил еще древнегреческий философ Платон, который утверждал, что душа и тело являются единым целым. Позже его идеи поддержали многие ученые, и сегодня все чаще становится понятно, что наши эмоции часто управляют нашим физическим состоянием.   Ключевые слова:защитные механизмы, онтогенез, психика, эмоции, субъективные переживания, стресс, адаптационные процессы, психосоматические расстройства, здоровье человека, иерархизованисть мотивам.